Service quality and customer satisfaction in a micro enterprise - Doza Rojas, Yessica Juana (2024)
Micro-enterprises are the most numerous in the world, but they must maintain their sustainability over time, facing various factors such as globalization, competition, changes in the economy, free market, among others. To do so, microenterprises will have to manage themselves to achieve products and/or services with optimal quality and achieve the desired customer satisfaction. For this reason, this research work had the objective of determining the relationship between service quality and customer satisfaction in the food and beverage microenterprise Mimo's, Chaclacayo 2021. The approach is quantitative, basic type, non-experimental design, cross-sectional correlational, descriptive correlational level and hypothetical deductive method. The population was 213 clients, determining a sample of 67 clients. For both variables, a questionnaire was used as a data collection instrument. In order to validate the objective, Spearman's Rho statistical test was used, reaching a value of p=0.000<0.05, so the alternative hypothesis that mentions that there is a significant relationship between service quality and customer satisfaction was accepted and gave a result of Rho=0.928, which confirms a very high positive correlation. It is recommended that Mimo's Food and Beverage Microenterprise continue to conduct periodic customer surveys on service quality and customer satisfaction so that with the results obtained, its managers can make decisions to improve quality and thus increase customer satisfaction.